2004
DOI: 10.1161/01.hyp.0000111832.47667.13
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Endothelium-Dependent NO-cGMP Vascular Relaxation and Hypertension in Growth-Restricted Rats on a High-Salt Diet

Abstract: Abstract-Low birth weight caused by placental insufficiency increases the risk of hypertension in young adults, particularly while ingesting a high-salt diet; however, the vascular mechanisms involved are unclear. We tested whether intrauterine fetal growth restriction results in salt-sensitive offspring that exhibit impaired endothelium-dependent relaxation, enhanced vascular contraction, and hypertension during high-salt diet feeding. Male offspring of control pregnant rats and pregnant rats with reduced ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
20
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 50 publications
6
20
1
1
Order By: Relevance
“…Interestingly, PE-evoked contraction was largely increased in the two groups of regimen when the endothelium was removed, and the difference between normal and HS groups vanished as reported by Payne et al (18). In addition, the response of denuded rings to KCl, which induces voltageactivated calcium entry from the extracellular space, and to caffeine, which mobilizes calcium from the sarcoplasmic reticulum, was markedly higher in the HS than in NS group.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Interestingly, PE-evoked contraction was largely increased in the two groups of regimen when the endothelium was removed, and the difference between normal and HS groups vanished as reported by Payne et al (18). In addition, the response of denuded rings to KCl, which induces voltageactivated calcium entry from the extracellular space, and to caffeine, which mobilizes calcium from the sarcoplasmic reticulum, was markedly higher in the HS than in NS group.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, an enhanced influence of nitric oxide (NO) may have a major role in the lack of rise in blood pressure of sodiumresistant rats when fed a HS diet. In the Dahl-resistant strain (16) and more clearly in the Sprague-Dawley rats (18), N Gnitro-L-arginine methyl ester (L-NAME) or 1H- [1,2,4]oxadiazolo [4,3-a]quinoxalin-1-one, a guanylate cyclase inhibitor, enhanced phenylephrine (PE) contraction, and to a greater extent in rats fed an HS than a normal salt (NS) diet. Taken together, these results favor an adaptive response of both the endothelium and the vascular smooth muscle cells to chronic HS intake in adult rats of resistant strains.…”
mentioning
confidence: 99%
“…In adult IUGR rats, endothelial dysfunction in association with a decrease in activity and expression of endothelial NO synthase was described [226,227] . Others have shown a diminished NO-dependent vasorelaxation [111,138,[228][229][230][231] . Deficiency of NO, induced by exogenous inhibition of NO generation by arginine analogues leads to hypertension [232][233][234] , and increased levels of PRA [234,235] , suggesting a role of RAS activation through endogenous NO inhibition after IUGR.…”
Section: Nitric Oxidementioning
confidence: 99%
“…The volume overload triggers suppression of the renin-angiotensin-aldosterone system, leading to increased salt and water excretion and restoration of vascular volume toward normal (10 -12, 23). High dietary sodium may also promote vasoconstriction by changing plasma osmolarity, nuclear localization, and increased nuclear expression of vasoconstrictive stimuli, such as endothelin-1, release of ouabainlike factor, and activation of the sodium/calcium exchange mechanisms (1,2,18,20,28). Other studies have suggested that high dietary sodium may also affect vascular nitric oxide (NO) production (9).…”
mentioning
confidence: 99%